Structure-guided unravelling: Phenolic hydroxyls contribute to reduction of acrylamide using multiplex quantitative structure–activity relationship modelling. (15th May 2016) - Zhang, Yu; Huang, Mengmeng; Wang, Qiao; Cheng, Jun
Highlights: Dose-dependent reduction of acrylamide by flavonoids shows bell-shaped correlation. Phenolic hydroxyls instead of alcoholic hydroxyls contribute to reduction effect. Number and position of phenolic hydroxyls correlates the reduction effect by QSAR. The study broadens understanding of acrylamide chemoprevention on a structural basis. Abstract: We reported a structure–activity relationship study on unravelling phenolic hydroxyls instead of alcoholic hydroxyls contribute to the reduction of acrylamide formation by flavonoids. The dose-dependent study shows a close correlation between the number of phenolic hydroxyls of flavonoids and their reduction effects. In view of positions of hydroxyls, the 3′, 4′(ortho)-dihydroxyls in B cycle, 3-hydroxyl or hydroxyls of 3-gallate in C cycle, and 5, 7(meta)-dihydroxyls in A cycle of flavonoid structures play an important role in the reduction of acrylamide. Flavone C-glycosides are more effective at reducing the formation of acrylamide than flavone O-glycosides when sharing the same aglycone. The current multiplex quantitative structure–activity relationship (QSAR) equations effectively predict the inhibitory rates of acrylamide using selected chemometric parameters ( R 2 : 0.835–0.938). This pioneer study opens a broad understanding on the chemoprevention of acrylamide contaminants on a structural basis.